Análisis de los construcción de estereotipos de género a través de los contenidos en la Plataforma Digital de Diario El Espectador, 2020 - 2021. - Delgado Guillen, Kerly Milena (2023)
This research work aims to analyze the construction of gender stereotypes through the digital platform of Diario el Espectador during the period 2020 - 2021. To generate the individual results of the work, use was made of several opinions proposed by experts on the subject of gender stereotypes, also in content analysis and complemented with specialized interviews. Based on the qualitative method, it was possible to determine specific unique characteristics of the contents found in Diario el Espectador, thus better observing the object of study. The research allowed us to analyze what is said, how it is said, and why it is said to have a better scope on how the construction of these contents was carried out. It was possible to corroborate the existence of the contents at the moment of entering the website of Diario el Espectador, so the research was well-directed to perform the content analysis. On the website, it was possible to find different informative notes, interviews, news, chronicles, etc. It should be emphasized that the media has a correct organization of its publications. Thus, it was possible to complement the information obtained with the specialized interviews and the statements of the different expert authors on the subject of gender stereotypes. Once the above was determined, the analysis manual was created, which will help to recognize the elements that construct gender stereotypes through the contents of digital platforms.